Bukids linking architecture and farming for the reintegration of youth drug dependents into the community - Manuel, Adelijoy C.; Evangelista, Alex Rey P. (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
Bukids is a project located at Los Baños, Laguna that challenges the conventional system for youth rehabilitation in the country. It aims to address the key issues present in our current facilities such as overcrowding, lack of equipment, and the prison-looking environment - these issues were proven to worsen their condition which results to more drug use when they are released. With this, the community-based approach was chosen as this type is the most suitable for children. This targets the emotional and social issues that led to drug use through group therapies. For a more holistic, recovery, this was combined with the concept of care farming which provides more opportunity for social interaction and physical activities in nature which reduce stress and is directly related to good mental health. Based on these concepts and the guidelines set by the Department of Health, the spaces were generated. The analysis of the user's behavior was also analyzed to seamlessly link the community and farming spaces without compromising security as well as to be connected, organic, and youth-centered. With the lack and inhumane condition of our current facilities, it is about time that we try better approaches which are evidence-based and culturally adaptive.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Youth Rehabilitation; Agriculture -- Study and Teaching -- Los Baños -- Laguna